Effect of microstructural evolution from nano to micron grain size regime towards structural, magnetic, electrical and microwave properties of gadolinium iron garnet (Gd3Fe5O12) - Farah Nabilah, Shafiee; Muhammad Syazwan, Mustaffa; Nor Hapishah, Abdullah; Mohd Nizar, Hamidon; Ismayadi, Ismail; Rodziah, Nazlan; Idza Riati, Ibrahim; Fadzidah, Mohd Idris; Mohd Shamsul Ezzad, Shafie (Springer, 2021)
The influence of microstructural changes from nano to micron grain size regime towards their structural, magnetic, electrical and microwave properties of gadolinium iron garnet (Gd3Fe5O12) has been investigated systematically in this research work. Raw materials were milled via high-energy ball milling (HEBM) followed by subsequent sintering (600–1400 °C) process. X-ray diffraction (XRD) analysis had shown that single phase with garnet structure and highest crystallinity of Gd3Fe5O12 was formed at 1000 °C. The B–H hysteresis loop unveil the evolution development of magnetic behaviour (paramagnetism–ferrimagnetism) in samples thru variation of different sintering temperature. The values of linewidth (∆H) can be grouped into two groups which are; sample increased from 600 to 1000 °C due to shape and strain induced anisotropy while decreasing from 1100 to 1400 °C influenced by magnetocrystalline anisotropy with the increment of the sintering temperature.